(untitled) (Mustansiria Dental Journal, 2005)
This study aimed to assess the caries-preventive potential of various chopped CO2 laser parameters, and to explore the effect of the laser energy density on the caries inhibition activity on enamel surface in vitro . Extracted human premolar teeth were irradiated with three various energy densities (25.47, 50.93, and 101.86) J/cm2, by changing the number of pulses, the pulse duration, and the spot diameter. The CO2 laser system emitted laser with 6.01 um in wavelength and l0Hz repetition rate. All teeth were subjected to carieslike lesion tbrmation by 3.5 pH lactic acid for 2l days. The teeth after that were sectioned into ground cross sections and the lesion depths were measured under a polarizing microscope . The result indicated that the chopped CO2 laser preventive treatments inhibited carieslike lesion progression up to 36%. This effect was improved with increased total energy density within the limits of the examined laser parameters